Handling of Children with Attention Deficit Hyperactivity Disorder (ADHD) from a Psychological and Islamic Perspective - Sofia Putri Wulandari; Abdul Muhid (al-Afkar, Journal For Islamic Studies, 2025)
This article is based on the pattern of handling children with Attention Deficit Hyperactivity Disorder (ADHD) seen from the perspective of Psychology and Islam. In this article will discuss a little about ADHD in terms of definition that includes factors, causes to treatment reviewed from the perspective of Psychology. Children with ADHD themselves are problems faced by children. These characteristics include difficulty in calming down, behaving aggressively, hyperactive, impulsive, difficulty controlling emotions, seeking attention, and difficulty focusing. In this article will also be seen briefly from the perspective of Education and Islam. This article uses a qualitative approach with a qualitative descriptive method, by carrying out a series of procedures that produce descriptive data that is in accordance with the theme of the discussion. In the data collection technique is applied with the technique of library analysis (library research) by describing all library sources in the form of documents, books, articles, journals related to Handling Children with Attention Deficit Hyperactivity Disorder (ADHD) Perspective of Psychology and Islam.